PREVALENCE OF CONGENITAL DISEASES AMONG CONSANGUINEOUS MARRIAGES IN DISTRICT PESHAWAR PAKISTAN - Sarwar, Naveeda; Nawaz, Rab; Abid, Saima; Hamza, Amir; Khan, Aimal; Durrani, Aiman; Khan, Waqas Saifullah (Annals of Allied Health Sciences, 2022)
Objective: To determine prevalence of congenital diseases among the consanguineous marriages. Material & Methods: A cross sectional study was carried out at the outpatient departments of the different private and public hospitals of Peshawar from November 2019 to April 2020. A total of 230 patients were interviewed using a closed ended questionnaire to obtain information on several dimensional effects of cousin marriages. The data was analyzed using SPSS 25. Results: A total 230 subjects participated in the study. Parents of 169 (73.5%) children had consanguineous marriage. 11(4.8%) children had Down Syndrome followed by congenital heart defects (n=13, 5.7%), thalassemia (n=190, 82.6%), mental retardation (n=5, 1.7%) and Charcot Marie Tooth Syndrome (n=12, 5.2%). Conclusion: Many patients suffered from the adverse effects of cousin marriage. It was concluded that lack of education, awareness, poverty, emphasis on cultural values were the reasons that had encouraged cousin marriages.